Influence of application of the inelastic taping in plantar pressure of runners pronators. - Rodrigues, Juliana Rocha; Craveiro, Wesley Albuquerque; Lemos, Thiago Vilela; Passos, Fábio Alessandro Galvão; Macedo, Osmair Gomes de; Matheus, João Paulo Chieregato (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Background: The excessive motion of subtalar pronation of the foot, can cause stress and burden in tissues of the region, giving origin to aches and microtrauma. In clinical practice, excessive movement has been limited to the use of techniques of bandages applied to the plantar arch. Objective: Was to analyze the influence of rigid bandage in plantar pressure distribution corridors pronators. Method: This is a randomized clinical trial, blinded, with twenty runners pronators (33±7 y, 71±7 kg, 174±6 cm). Technique was applied bandage (rigid - BR) to support the plantar arch, described as antipronation. Plantar pressure data were collected using the F -scan system in three tests run at 9 km/h being: no bandages, rigid taping. We considered seven areas of pressure for data analysis, performed by means of ANOVA for repeated measures followed by paired t test. Results: BR resulted in significant reductions (p<0.05) in contact pressures and peak pressure rearfoot. Conclusion: Thus, we conclude that BR provided decrease in contact pressures and peak pressure foot, being significant on the hindfoot than in the midfoot.